Is the systemic administration of arnica extracts safe? A systematic review of preclinical trials (Research, Society and Development, 2021)
“Arnica” extracts are widely used in folk medicine to treat acute and chronic inflammatory ailments. Nevertheless, their toxic effects upon systemic use are still not fully understood. Therefore, this work provides a systematic review on the safety of arnica extracts following preclinical trials covering their oral and intraperitoneal administration in animal models. Henceforth, PRISMA guideline was followed and the study protocol was registered in PROSPERO (CDR42020167112). Searches were performed in PubMed (MEDLINE), Scopus, Science Direct, Web of Science (Science Citation Index), and Health Virtual Library (BVS) databases; while SYRCLE’s Risk of Bias tool and CAMARADES checklist were used to assess scientific quality. From 382 articles, five studies met eligibility criteria and underwent qualitative analysis. Data of acute toxicity was reported in all the selected articles, and the treatment time was up to 14 days. Moreover, the following species were reported: Solidago chilensis (hazard categories of 4 and 5 for i.p and v.o administration, respectively); Solidago microglossa (hazard category of 3, i.p); Lychnophora trichocarpha (hazard category of ≥ 4, i.p); and Lychnophora pinaster (hazard category of ≥ 4, v.o). The alcoholic extracts showcased greater toxic potential, which increased in a dose-dependent manner after 100 mg/Kg. Concerning organ-specific toxicity, the articles reported hepatotoxicity and nephrotoxicity following histopathological analysis. However, the safety of S. chilensis, L. pinaster, L. trichocarpha, and S. microglossa following systemic administration remains unclear due to the limited experimental quality of the included papers, as well as the lack of reported chronic toxicity, pharmacokinetics, and mutagenicity studies.